Functional genomics reveals increases in cholesterol biosynthetic genes and highly unsaturated fatty acid biosynthesis after dietary substitution of fish oil with vegetable oils in Atlantic salmon (Salmo salar) - Leaver, Michael; Villeneuve, Laure; Obach, Alex; Jensen, Linda; Bron, James; Tocher, Douglas R; Taggart, John (BMC Genomics, 2008)
Background: There is an increasing drive to replace fish oil (FO) in finfish aquaculture diets with vegetable oils (VO), driven by the short supply of FO derived from wild fish stocks. However, little is known of the consequences for fish health after such substitution. The effect of dietary VO on hepatic gene expression, lipid composition and growth was determined in Atlantic salmon (Salmo salar), using a combination of cDNA microarray, lipid, and biochemical analysis. FO was replaced with VO, added to diets as rapeseed (RO), soybean (SO) or linseed (LO) oils. Results: Dietary VO had no major effect on growth of the fish, but increased the whole fish protein contents and tended to decrease whole fish lipid content, thus increasing the protein:lipid ratio. Expression levels of genes of the highly unsaturated fatty acid (HUFA) and cholesterol biosynthetic pathways were increased in all vegetable oil diets as was SREBP2, a master transcriptional regulator of these pathways. Other genes whose expression was increased by feeding VO included those of NADPH generation, lipid transport, peroxisomal fatty acid oxidation, a marker of intracellular lipid accumulation, and protein and RNA processing. Consistent with these results, HUFA biosynthesis, hepatic β-oxidation activity and enzymic NADPH production were changed by VO, and there was a trend for increased hepatic lipid in LO and SO diets. Tissue cholesterol levels in VO fed fish were the same as animals fed FO, whereas fatty acid composition of the tissues largely reflected those of the diets and was marked by enrichment of 18 carbon fatty acids and reductions in 20 and 22 carbon HUFA. Conclusion: This combined gene expression, compositional and metabolic study demonstrates that major lipid metabolic effects occur after replacing FO with VO in salmon diets. These effects are most likely mediated by SREBP2, which responds to reductions in dietary cholesterol. These changes are sufficient to maintain whole body cholesterol levels but not HUFA levels.